2022
DOI: 10.1097/md.0000000000030755
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine to absolute lymphocyte count ratio effectively risk stratifies patients who require intensive care in hospitalized patients with coronavirus disease 2019

Abstract: Patients with preexisting kidney disease or acute kidney injury had poorer outcomes in coronavirus disease 2019 illness. Lymphopenia was associated with more severe illness. Risk stratification with simple laboratory tests may help appropriate site patients in a cost-effective manner and ease the burden on healthcare systems. We examined a ratio of serum creatinine level to absolute lymphocyte count at presentation (creatinine-lymphocyte ratio, CLR) in predicting outcomes in hospitalized patients with COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Among patients hospitalized with Omicron XBB SARS‐CoV‐2, we observed that advanced age and the presence of chronic kidney disease predicted adverse outcomes. Previously reported markers such as radiographic evidence of pneumonia, elevated C‐reactive protein, and serum creatinine levels at presentation also correlated with adverse outcomes 6,7 . In our hospitalized cohort, there were no observable differences in outcomes with any specific Omicron XBB sublineage, and with prevalence similar to trends from national surveillance data, where XBB.1.16 (23%) and XBB.2.3 (29.5%) were also the commonest (unpublished data from Ministry of Health, Singapore).…”
Section: Parameter Moderate‐to‐severe Illness (Required Supplemental ...supporting
confidence: 75%
See 1 more Smart Citation
“…Among patients hospitalized with Omicron XBB SARS‐CoV‐2, we observed that advanced age and the presence of chronic kidney disease predicted adverse outcomes. Previously reported markers such as radiographic evidence of pneumonia, elevated C‐reactive protein, and serum creatinine levels at presentation also correlated with adverse outcomes 6,7 . In our hospitalized cohort, there were no observable differences in outcomes with any specific Omicron XBB sublineage, and with prevalence similar to trends from national surveillance data, where XBB.1.16 (23%) and XBB.2.3 (29.5%) were also the commonest (unpublished data from Ministry of Health, Singapore).…”
Section: Parameter Moderate‐to‐severe Illness (Required Supplemental ...supporting
confidence: 75%
“…Previously reported markers such as radiographic evidence of pneumonia, elevated Creactive protein, and serum creatinine levels at presentation also correlated with adverse outcomes. 6,7 In our hospitalized cohort, there were no observable differences in outcomes with any specific Omicron XBB sublineage, and with prevalence similar to trends from national surveillance data, where XBB.…”
supporting
confidence: 62%
“…Our findings showed that SARS-CoV-2 has different effects on individual patients, and we found these can be predicted more accurately by their inflammatory status than by age, comorbidities, and viral load, which were consistently associated with severe disease in the COVID-19 literature [25] . That the hyperinflammatory phenotype is a stronger predictor of progression to more severe disease may be explained by the association of inflammation with dysfunction in other organ systems beyond the respiratory system, such as the heart, lungs, and kidneys [26 , 27] .…”
Section: Discussionmentioning
confidence: 99%
“…We had previously examined the varied clinical manifestations of acute COVID-19 and shown that multiple organ systems, beyond the lungs, can be affected. In a moderately sized, retrospective cohort of hospitalised patients with mild COVID-19, consisting of primarily young and immunocompetent migrant workers in Singapore, we had observed that the infection can present with multi-system involvement, including cardiac manifestations,[ 4 ] kidney injury,[ 5 ] altered haematological profile[ 6 ] and elevated liver enzymes. [ 7 ] While some of these organ-specific complications may be related to the uncontrolled host inflammatory response to the viral infection, a majority of the patients we had examined were largely afebrile, asymptomatic and with relatively mild disease.…”
mentioning
confidence: 99%